Should Brazil invest in Small Modular Reactor? - Valéria Emiliana Alcântara e Alves; Daniel José Leibing Sarney; Amir Zacarias Mesquita; Vitor Fernandes; Ana Rosa Baliza (Brazilian Journal of Radiation Sciences)
Brazil exhibits a diversified energy matrix, with 88% coming from renewable sources in 2022, prominently hydroelectricity at 64%. However, climatic vulnerability due to dependence on water for electricity generation poses a challenge during periods of low precipitation. Most consumers are integrated into the National Interconnected System (SIN), while isolated systems, especially in the Amazon region, are managed by the National System Operator (ONS). Over 80% of the country's electricity demand is met by the industrial, residential, and commercial sectors. Despite the modest share of nuclear energy in the national electricity grid, Brazil holds the 8th largest global uranium reserves, suggesting significant potential for expanding this low-carbon option. Small Modular Reactors (SMRs) represent a relevant innovation. With capacities of up to 300 MWe per unit, SMRs are designed to be more economical, secure, and require less refueling compared to conventional reactors. Their modular design allows for factory assembly and simplified transport, making them particularly suitable for remote areas, offering a reliable base load energy source. The ability of SMRs to adjust to electricity demand and operate flexibly positions them as a complementary alternative to renewable sources, which are more susceptible to external climate variations.